Price Caps versus Reimbursement Limits: Pharmaceutical Regulation under Market Integration through Parallel Trade - Laura Birg (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
In this paper, I study the effect of parallel trade (cross border resale of goods without the authorization of the manufacturer) on pharmaceutical regulation in a North-South framework with a firm's endogenous decision to export to the South. Governments in both countries may limit prices directly via price caps or restrict third-party payer reimbursement for the drug via reimbursement limits. Parallel trade may relax regulation in the source country of parallel imports (South) and intensify regulation in the destination country (North): In the source country, parallel trade may relax regulation both under a price cap and a reimbursement limit under certain conditions. In the destination country, parallel trade has no effect on the level of regulation under a price cap, and it intensifies regulation under a reimbursement limit. Parallel trade may change regulatory preferences: Under no parallel trade, both the source and destination country set prices caps. Under parallel trade, the source country sets a price cap, but the destination country sets a reimbursement, thereby enforcing a higher price cap in the South. This implies higher drug prices under parallel trade in both source and destination country.
Keywords: F12; I11; I18; 330; pharmaceutical regulation; price cap; reimbursement limit; parallel trade